Highly efficient removal of aluminum, iron, and manganese ions using Linde type-A zeolite obtained from hazardous waste. (March 2021) - Lobo-Recio, María Ángeles; Rodrigues, Caroline; Custódio Jeremias, Thamires; Lapolli, Flávio Rubens; Padilla, Isabel; López-Delgado, Aurora
Abstract: Coal acid mine drainage (AMD) contaminates natural water to form mine-impacted water (MIW), which is characterized by high levels of acidity, sulfate, and metallic ions. This study investigates the use of a Linde Type-A (LTA) zeolite obtained from a hazardous industrial waste for Al 3+, Fe 2+, and Mn 2+ removal from synthetic aqueous solutions. The aim of this study is to stablish a basis for the subsequent treatment of MIW in order to obtain reuse water. In a central composite rotatable design (CCRD) study, 8.25 g L −1 zeolite and 147 rpm were the optimal conditions for treating the multicomponent solution, yielding 99.9, 99.9 and 99.3% removal for Al 3+, Fe 2+, and Mn 2+, respectively. Isothermal studies showed that the affinity of the ions by the zeolite were ranked as Al 3+ >Mn 2+ >Fe 2+ . The best fitting isothermal models for monocomponent solutions were Tóth, Freundlich, and Sips for Al 3+, Fe 2+, and Mn 2+, respectively. In the multicomponent solution, Sips and Freundlich were the better fitting models for Al 3+ and Mn 2+, respectively, indicating a weakness of the sorbate-sorbent interactions. Kinetic studies revealed that the quantitative removal of Al 3+ was achieved in 5 min. The multicomponent solution was transformed into water that was suitable for non-potable use after an optimal time of 60 min. The results demonstrate that LTA zeolite synthetized from hazardous waste has a high potential for remediating contaminated water by metallic ions at low dosages and short times. Using LTA zeolite for remediating contaminated water could make a positive contribution to the circular economy and environmental sustainability. Graphical abstract: Image 1 Highlights: A new eco-friendly Linde Type-A (LTA) zeolite was used to remove toxic metal ions. Al 3+, Fe 2+ and Mn 2+ were removed from mimetic solutions of coal mine impacted water. Optimal treatment conditions were determined by a statistical factorial planning. Low LTA doses and short contact times were enough to get nearly quantitative removals. Results showed the high potential of LTA zeolite for treating real MIW in high scale.